PERANCANGAN BUSINESS MODEL CANVAS DESA WISATA KAMPUNG SEPATU CIBADUYUT - Hasbi, Imanuddin; Madiawati, Putu Nina; Jamiat, Nuslih; Kuswanto, Arif (CV Widina Media Utama, 2024)
The purpose of this research is to conduct a Business Model Canvas approach in designing a sustainable strategy in developing a tourist village in Kampung Sepatu by describing and defining each main activity to create value to generate income for the Village-Owned Enterprises (BUMDES) of Cangkuang Kulon Village. This type of research uses a qualitative research approach with SWOT analysis and Business Model Canvas. Respondents used key informants from business actors, community leaders, and local government officials. There are nine main activities in determining business development strategies to increase product value and income of business actors in Kampung Sepatu Cibaduyut Kulon Village. Study limitations in Cangkuang Kulon Village. This research is designed for a sustainable business development strategy specifically for Kampung Sepatu Tourism Village, Cangkuang Kulon Village, by defining the problems of shoe craftsmen and paying attention to local conditions so that the research results can be applied directly to shoe craftsmen in Kampung Sepatu, Cangkuang Kulon Village.ABSTRAKTujuan dari Peneliti ini adalah melakukan pendekatan Business Model Canvas dalam merancang strategi berkelanjutan dalam mengembangkan desa wisata di Kampung Sepatu dengan mendeskripsikan dan mendefinisikan setiap aktivitas utama untuk menciptakan nilai guna menghasilkan pendapatan bagi Badan Usaha Milik Desa (BUMDES) Desa Cangkuang Kulon. Jenis penelitian ini menggunakan pendekatan penelitian kualitatif dengan analisis SWOT dan Business Model Canvas. Responden menggunakan informan kunci dari pelaku usaha, tokoh masyarakat, dan pejabat pemerintah daerah. Terdapat sembilan kegiatan utama dalam menetapkan strategi pengembangan usaha untuk meningkatkan nilai produk dan pendapatan pelaku usaha di Kampung Sepatu Desa Cibaduyut Kulon. Keterbatasan studi di Desa Cangkuang Kulon. Penelitian ini dirancang untuk strategi pengembangan usaha yang berkelanjutan khusus untuk Desa Wisata Kampung Sepatu, Desa Cangkuang Kulon, dengan mendefinisikan permasalahan pengrajin sepatu dan memperhatikan kondisi lokal sehingga hasil penelitian dapat diterapkan langsung pada pengrajin sepatu di Kampung Sepatu, Desa Cangkuang Kulon.